Immunohistochemical expression of IL-1β, IL-6, and NF-κβ in fibroids - de Mezer, Mateusz; Dolata, Natalia; Markowska, Janina; Krzyżaniak, Monika; Naskręt-Grochowalska, Agnieszka; Żurawski, Jakub; Markowska, Anna (Frontiers in Immunology, 2025)
Uterine fibroids are benign tumors that occur in a large proportion of women and interfere with the proper functioning of this organ. One of the factors leading to these proliferative changes appears to be the appearance of extracellular matrix (ECM) fibrosis at the site of local inflammatory foci. Due to the potential impact of cytokines in this process, it is interesting to determine their expression levels in fibroids and surrounding tissues, which may contribute to a better understanding of the mechanisms leading to the formation of these tumors. In tissue material from 50 women with uterine fibroids who underwent hysterectomy and 45 women operated on for other reasons (most often prolapse of the reproductive organ), the concentration of inflammatory cytokines IL-1β and IL-6 and the concentration of the transcription nuclear factor NF-κβ were determined. The tissue from the fibroid, the peripheral myometrium, and the unchanged myometrium were examined in women who underwent surgery for reasons other than uterine fibroids. A significant decrease in IL-1β levels was observed in the center of the fibroid compared to both peripheral and control muscle tissue (p=0.001). The concentrations of IL-6 were found to be similar across all three locations examined. The NF-κβ levels were significantly lower in the fibroid and peripheral tissues (p<0.001) compared to the control group. The concentration of IL-1β was found to be significantly and positively correlated with the concentration of NF-κβ in uterine fibroids.